(3OjhGf GdHcQj GdUOjbjs - (3GdHcQj , eMeO Hf eMeO CHj GdMSf Hf eMeO Hf YHO GdQMef, TeS GdOjf CHh GdecGQe,J (B994 (3g` s
(3ChdgG (B:s
(3MQa GdgeRI(B: (3bGd bOS Gddg SQg eG XHGA HbGYI GdhYSGA hedGM HCjef GdLQYGA s
(3BNQgG (B:s
(3hbGd QVj Gddg Yfg(B: (3fTQ GdaQb CfGSkG aGZJOhG aj EMJLGH hWhGfj GdLeY Wj s
(3fSNI KGfjIs
(3JfbU GdebOeIs
(3hKdGK ebWhYGJ ef BNQgG hJfJgj aj U (B150 (3hjdjgG YTQ UaMGJ aj McGjGJ dHYV GdUGdMjf hGdRgGOs
(3hQO CjVkG JMJ Qbe (B2092 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B60 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B281s
Keywords: (3GdCOHs